Historical biogeography of a Brazilian lineage of Tillandsioideae (subtribe Vrieseinae, Bromeliaceae): the Paranaean Sea hypothesized as the main vicariant event. (24th August 2019) - Kessous, Igor M; Neves, Beatriz; Couto, Dayvid R; Paixão-Souza, Bruno; Pederneiras, Leandro C; Moura, Ricardo L; Barfuss, Michael H J; Salgueiro, Fabiano; Costa, Andrea F
Abstract: Subtribe Vrieseinae comprise four genera, Alcantarea, Stigmatodon, Vriesea s.s. and Waltillia, encompassing c . 20% of species in Tillandsioideae (Bromeliaceae), almost all of which are exclusive to Brazil. Here, we explore the biogeographic history of Vrieseinae, sampling 21 of the 22 genera of Tillandsioideae (130 terminals) and three DNA sequence markers (two plastid: rps16-trnK and matK ; one nuclear: PHYC ). We inferred a dated phylogeny and the ancestral areas of this lineage through RASP (reconstruct ancestral state in phylogeny) analyses. Vrieseinae were recovered as monophyletic, but tribe Vrieseeae (subtribe Vrieseinae + subtribe Cipuropsidinae) were not. A vicariant event between the Andes and Brazilian Shield probably occurred c. 10 Mya, when two clades, Cipuropsidineae + Tillandsieae and Vrieseineae, diverged. The Atlantic Forest plus the Chacoan region is recognized as the ancestral area for Vrieseinae. The results confirmed the recent origin of genera of Vrieseinae, with estimated crown ages in the Pliocene (5.3–2.6 Mya). We propose that the Paranaean Sea influenced the divergence of the main clades; Pleistocene events were probably responsible for the diversification of the most recent clades. This study sheds light on the biogeographic history of a key group of Neotropical plants, providing a new hypothesis for the evolution of bromeliads.